Comparison of impulsive wave forces on a semi-submerged platform deck, with and without columns and considering air compressibility effects, under regular wave actions - Zhai, G. (Taylor and Francis Ltd., 2021)
The decks of oil-extractingÂ platforms could be damaged by great wave impact loads under harsh ocean conditions. Our understanding of the pressure distribution characteristics under the deck, especially those influenced by columns, is incomplete. A series of experiments are carried out to study the spatial and instantaneous distribution of the impact pressure generated by regular waves acting on the deck, and two cases are considered: a flat plate (FP for short) and a plate with four vertical columns (CP for short). Three-dimensional numerical simulations using a modified wave generating tool are conducted and compared to experimental data. Both compressible and incompressible flow solvers are applied to further quantitatively analyse the effect of air compressibility on impacting forces. The results show marked changes in both the pressure distribution scatter under the deck and the magnitude of the impact pressureÂ when comparing the two cases. It has been demonstrated that run-up along the columns can cause intense localized pressure on the deck, and a close relationship exists between this increased pressure and fluid velocity. Additionally, the preliminaryÂ results showed that the phase compressibility increases the peak pressure compared with that of an incompressible solver, and the former matches the experimental measurements better. Â© 2021 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.